Business Incubators Support College Performance - I Ketut Sutama; I Ketut Pasek; I Gede Mudana (Politeknik Negeri Bali, 2018)
Business incubators have a very important role in developing entrepreneurship, since it gives large opportunity to its participants to develop their business skill during incubation. The Indonesian government today provides a major boost to the development of business incubators in universities or other form of higher education institutions. The purpose of this research is to analyze the validation of the establishment of business incubator in colleges. In Ministerial Regulation (Permen) Minister of Cooperation and Small Medium Entrepreneurship the Republic of Indonesia No. 24/2015 explained that the head of the university, the Rector or the Director may issue a business incubators license. Thus, internal validation can be done by university or college management through the issuance of Decree (SK) Establishment complete with personnel appointed as manager. Furthermore, the college, has to provide a place or room consisting of office space, tenant room at least 3, discussion room 1, and tenant production display room. External validation is carried out by tenants through their success of becoming independent businessmen after being forged or incubated in a business incubator for a maximum of 3 years in one incubation period.